Answer: P = 0
Step-by-step explanation:
Solve for p by simplifying both sides of the equation, the isolating the variable.
-2p + 10p = 7p, P will equal 0.
***If you found my answer helpful, please give me the brainliest. :) ***
Answer:
left 1 unit, up 5 units
Step-by-step explanation:
First factor
g(x)=x^2+2x+6 = (x+1)^2+5
The standard transformation formula is
g(x) = a*f(bx-h) + k
which means
a=1, b=1,h=-1, k=5
or
h=-1 means translate left one unit
k=5 means translate up 5 units.
Choose the first option: left 1 unit, up 5 units
Answer:
(3x+2)(2x+3)
Step-by-step explanation:
6x2+13x+6
6x2+13x+6
=(3x+2)(2x+3)
5 lbs of apples x pounds of apples---------------------- = ----------------------------2 cups of sugar 4/3 cup of sugar Solve for x.
Answer:
-3x^{4} + 19x^{3} - 38x^{2} + 25x - 3
Step-by-step explanation:
1) distribute x² into (-3x² + 7x - 1) to get: -3x^{4} + 7x³ - x²
2) distribute -4x into (-3x² + 7x - 1) to get: 12x³ - 28x + 4x
3) distribute 3 into (-3x² + 7x - 1) to get: -9x² + 21x - 3
4) combine all the answers together into one equation:
-3x^{4} + 7x³ - x² + 12x³ - 28x² + 4x - 9x² + 21x - 3
5) combine like terms:
7x³ + 12x³ = 19x³
-x² + -28x² + -9x² = -38x²
4x + 21x = 25x
6) combine answers together into one equation:
-3x^{4} + 19x³ - 38x² + 25x - 3